Pengaruh Brand Image, Product Quality dan Price terhadap Loyalitas Konsumen pada Sepatu Olahraga : (Studi pada Atlet Basket di Kota Medan) - Muhammad Ayman Ashari; Hafiza Adlina; Onan Marakali Siregar (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of brand image, product quality, and price on consumer loyalty toward sports shoes among basketball athletes in Medan City. The research employed a quantitative approach with an associative design by distributing questionnaires to 78 respondents. The results indicate that brand image has no significant effect on consumer loyalty, while product quality and price show a positive influence. Simultaneously, the three variables contribute to the formation of consumer loyalty, particularly through usage satisfaction, repurchase intention, and recommendations to others. These findings highlight the importance of product quality and competitive pricing as the main factors in building consumer loyalty in the sports shoe market. This research provides insights for athletic shoe manufacturers to focus more on improving product quality and competitive pricing to maintain and expand market share among athletes. It also shows that while brand image can influence consumer perceptions, quality and price are more dominant in building long-term relationships with consumers in the athletic shoe industry.